Pendidikan Kesehatan Reproduksi Remaja dengan Media Pemanfaatan Buku Rapor Kesehatanku - Greiny Arisani; Wahidah Sukriani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Adolescence is a sensitive development or critical period for normative and maladaptive development patterns. Reproductive health is an essential issue for adolescents because every phase of adolescent development has developmental tasks that must be fulfilled. Implementing the activity is a combination of health education and peer group discussion using my health report book as the media. The results of community service activities were four teenagers (20%) who were at the level of knowledge both before being given health education and peer group discussions with my health report book media and after being shown an increase of 17 teenagers (85%). Then as many as seven teenagers (35%) were at the level of sufficient knowledge before being given health education and peer group discussion with my health report book media. After being offered only three teenagers (15%) who were at the level of sufficient knowledge. At the level of lack of knowledge before being given counseling and peer group discussion with my health report book media as many as nine teenagers (45%) at level of lack of knowledge and after being given, there were no teenagers at the level of lack of knowledge so it can be concluded that the combination of health education and peer group discussion with media My health report card is an alternative choice in increasing adolescent knowledge about reproductive health.